Wind-Controlled Transport of Saltwater in the Southeastern Baltic Sea: A Model Study - Zhurbas, Victor; Väli, Germo (Frontiers in Marine Science, 2022)
We hypothesized that the saltwater transport in a system of the southeastern Baltic basins including the Gdańsk and Gotland deeps connected by the Hoburg Channel, is greatly controlled by wind forcing, which has a clear physical explanation. Namely, the westerly winds develop the Ekman transport in the upper layer to the south from the Gotland Deep to the Gdańsk Deep which causes a compensatory saltwater countercurrent in the deep layer to the north from the Gdańsk Deep towards the Gotland Deep, and, vice versa, the easterly winds develop the Ekman transport to the north from the Gdańsk Deep towards the Gotland Deep causing a compensatory saltwater countercurrent in the deep layer to the south from the Gotland Deep to the Gdańsk Deep. To confirm the hypothesis, results of numerical modelling of the Baltic Sea circulation for a 10-yr period (2010–2019) are applied. The daily saltwater transport to the northeast through a cross-section of the Hoburg Channel is found to be highly correlated with the wind stress component towards southeast (the correlation coefficient is 0.812) which can be considered as a straightforward confirmation of the hypothesis indicating the strong wind-driven circulation also in the deep layers of the Baltic Sea. Estimates of the daily saltwater transport through the above-mentioned and several other cross-sections of the southeastern Baltic Sea basins confirm a rule stating that the maximum correlation takes place between the saltwater transport and a wind stress component directed perpendicularly to the right relative to the direction of saltwater transport.